THE DENSITY OF STATES OF A SPATIALLY DISORDERED SYSTEM - THEORY COMPARED WITH SIMULATION - Bush, I; Logan, D; Madden, P; Winn, M (1989)
The adequacy and range of applicability of an analytically soluble single site theory for the density of states of a spatially disordered system is assessed by comparison with numerical simulations on an off-diagonally disordered tight-binding model. The validity of a non-single site theory, appropriate in the low-density domain, is also examined by comparison with simulation.